The juxtamembrane domain of StkP is phosphorylated and influences cell division in Streptococcus pneumoniae - Mélisse Hamidi; Sathya Narayanan Nagarajan; Vaishnavi Ravikumar; Virginie Gueguen-Chaignon; Cédric Laguri; Céline Freton; Ivan Mijakovic; Jean-Pierre Simorre; Stéphanie Ravaud; Christophe Grangeasse (mBio)
ABSTRACT Eukaryotic-like membrane Ser/Thr protein kinases play a pivotal role in different aspects of bacterial physiology. In contrast to the diversity of their extracellular domains, their cytoplasmic catalytic domains are highly conserved. However, the function of a long juxtamembrane domain (JMD), which connects the catalytic domain to the transmembrane helix, remains elusive. In this study, we investigated the function of the JMD of the Ser/Thr protein kinase StkP in the cell division of Streptococcus pneumoniae. We observed that the deletion of the JMD affected the ability of StkP to phosphorylate some of its endogenous substrates, thereby resulting in significant cell morphogenesis defects. Furthermore, multiple threonine residues were identified as being phosphorylated in the JMD. To investigate the functional significance of these phosphorylation sites, we conducted an integrative analysis, combining structural biology, proteomics, and bacterial cell imaging. Our results revealed that the phosphorylation of the JMD did not perturb the phosphorylation of StkP substrates. However, we observed that it modulated the timing of StkP localization to the division septum and the dynamics of cell constriction. We further demonstrated that phosphorylation of the JMD facilitated the recruitment of several cell division proteins, suggesting that it is required to assemble the division machinery at the division septum. In conclusion, this study demonstrates that the function of the JMD of StkP is modulated by phosphorylation and is critical for the cell division of S. pneumoniae. These observations may serve as a model for understanding the regulatory function of other bacterial Ser/Thr protein kinases.IMPORTANCEHow bacterial serine/threonine protein kinases are activated remains highly debated. In particular, models rely on the observations made with their eukaryotic counterparts, and only a few studies have investigated the molecular activation mechanism of bacterial serine/threonine protein kinases. This is particularly the case with regard to the juxtamembrane domain (JMD), which is proposed to contribute to kinase activation in numerous eukaryotic kinases. This study demonstrates that the juxtamembrane domain is likely not essential for the activation of the serine/threonine protein kinase StkP of S. pneumoniae. Rather, our findings reveal that it is required for cell division, where its phosphorylation affects the assembly of the division machinery at the division septum. These observations allow us to assign a function to the JMD in StkP-mediated regulation of pneumococcal cell division, thereby providing a new avenue for understanding the contribution of membrane serine/threonine protein kinases in the physiology of other bacteria.